Pengembangan Media Pembelajaran Tebak Kata Pada Materi Bank Sentral, Sistem Pembayaran dan Alat Pembayaran - Andriani, Ineke Devi; Dewi, Retno Mustika (Universitas Negeri Surabaya, 2021)
This research was conducted as an effort for students so that they can actively participate in learning. The learning media for guessing the word are presented in an attractive manner so that students can play while learning. The purpose of this research is to develop a product in the form of learning media for word guessing in order to improve learning outcomes. This type of research is development research using the 4D model which is limited to the develop stage. The data collection instrument used questionnaire guidelines by analyzing the validation results that were calculated using a Likert scale. The results of the test show that the media for guessing words on the material of the central bank, payment systems, and payment instruments have criteria that are suitable for use as a medium for economic learning. So that the media is declared feasible to be applied in class ten economic learning.